Meta-Analysis of COVID-19 Spread in Meat Processing Plants and Recommended Practical Actions - Abdolkazem Neisi; Gholamreza Goudarzi; Aliakbar Babaei; Vafa Hamid; Seyede Kosar Mousavi; Parnia Kanani; Niloufar Lajmorak; Heydar Maleki (Hamadan University of Medical Sciences, 2022)
Recently, the spread of the coronavirus disease 2019 (COVID-19) has increased among workers of meat processing plants (MPPs) around the world. This study reviewed the possible routes of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission and useful actions against it in slaughterhouses. The results revealed that the main factors for the spread of the virus included low indoor temperature, crowded area, wrong standing along production lines, contamination of high-touch surfaces, difficult education of workers with diverse native languages, low financial income, large MPPs with over 10 million Ib of packed meat per month, higher speed of production lines with 175 birds/minute, temporary contract of the workers, and weak approach of some meat processing companies against COVID-19 infection such as National Beef. COVID-19 transmission rate was 24 times higher among the workers of MPPs than among the population of the US. The practical actions against the spread of the virus were mainly marker using for remembering the previous location, mandatory mask use, especially FFP2/3 masks, and decentralization of large MPPs. By using the results of this study, slaughterhouse managers would be able to significantly control the spread of SARS-CoV-2 and future bio-threats to workers of MPPs and even to society.